Expression and localisation of insulin receptor substrate 2 in normal intestine and colorectal tumours. Regulation by intestine-specific transcription factor CDX2. Issue 9 (15th February 2009) - Modica, S; Morgano, A; Salvatore, L; Petruzzelli, M; Vanier, M-T; Valanzano, R; Esposito, D L; Palasciano, G; Duluc, I; Freund, J-N; Mariani-Costantini, R; Moschetta, A
Abstract : Background and aims: Self-renewal and differentiation of intestinal epithelium is a tightly regulated process, whose perturbations are implicated in human colorectal tumourigenesis. The insulin/insulin-like growth factor (IGF) signalling pathway may play an important role in intestinal epithelium homeostasis. Insulin receptor substrate 2 (IRS2) is a poorly characterised component in this pathway. Methods: Using complementary in vitro and in vivo human and murine models, expression (mRNA and protein levels), localisation (immunohistochemistry) and regulation of IRS2 were investigated in the normal intestine and colorectal tumours. In silico analysis of the human IRS2 promoter was performed together with reporter and chromatin immunoprecipitation assays. Results: Significant IRS2 expression was detected in the intestine, with specific protein localisation in the villus region of the ileum and in the surface epithelium of the colon. In human HT29 and Caco2 cells, IRS2 mRNA levels increased with spontaneous and induced differentiation, together with CDX2 (caudal-related homeobox protein 2), P21 and KLF4 (Krüppel-like factor 4). Adenoviral infection with human CDX2 induced IRS2 expression in APC- (adenomatous polyposis coli) and β-catenin-mutated cells. On the other hand, IRS2 downregulation was observed in differentiated enterocytes after adenoviral infection with short hairpin CDX2 (shCDX2), in the intestine of CDX2 heterozygous mice and in colorectal tumours of Apc Min/+ and patients with familial adenomatous polyposis (FAP). The human IRS2 promoter region presents several CDX2-binding sites where CDX2 immunoprecipitated in vivo. IRS2 reporters were functionally activated via CDX2 and blocked via a dominant-negative CDX2 protein. Conclusions: Combining gain- and loss-of-function approaches, an intriguing scenario is presented whereby IRS2 is significantly expressed in the apical intestinal compartment and is directly controlled by CDX2 in normal intestine and tumours.